Burden in the Eye of the Beholder: Why Should Administration Care?. Issue 166 (January 2016) - Ma, Yanli; Kulich, James; Hu, Shouping
Abstract : This chapter focuses on perspectives of external data reporting and their implications for institutional research offices and campuses as a whole. The authors examine a variety of uses for externally reported data and explore opportunities for using these data more fully across the institution.